Geopolitical Position of the PR of China – State and Perspectives - Mirković, Vladan M; Stajić, Ljubomir; Radivojević, Nenad (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
The territory of the People's Republic of China (PRC) has traditionally been perceived in geopolitical theories as part of the inner or marginal (land) crescent, which surrounds the core (pivot) of the Eurasian continent. Тhe interests of naval and land powers clash in this belt in order to secure global dominance. The rapid economic and social development of the PRC in the last three decades enabled it to launch the "Belt and Road" Initiative, which should result in the political, economic, cultural and infrastructural connection of the countries encompassed by this project. The fulfilment of the planned projects would provide the PRC with an exit from the geographical ring, by land to the west and by sea to the east and southeast, thus removing geographical obstacles to become a globally dominant power both on land and at sea. In such circumstances, traditional geopolitical patterns and the international order would also change. In this regard, the article analyzed the factors that influence on the geopolitical position of the PRC with a scientific prediction of that position in case of full implementation of the "Belt and Road" Initiative.
Keywords: geopolitics, the People's Republic of China, international order, international security, international relations